2003
DOI: 10.1002/jcb.10477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bafilomycin A1: An inhibitor of vacuolar H (+)‐ATPases on endocytosis and apoptosis in RAW cells and RAW cell‐derived osteoclasts

Abstract: Bafilomycin A1, a specific inhibitor of V-ATPases, is a potent inhibitor of bone resorption, but the underlying mechanisms of its action remain unclear. In this study, we investigated the effect of Bafilomycin A1 on endocytosis and apoptosis in RAW cells and RAW cell-derived osteoclasts. Quantitative analysis by flow cytometry showed that Bafilomycin A1 increased total transferrin levels when RAW cells were exposed to labeled transferrin and decreased the total uptake of Dextran-rhodamine B, both in a dose- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
64
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 47 publications
12
64
0
Order By: Relevance
“…Previous studies showed that macrophages from different origins and species express V-ATPase and respond to VATPase inhibitors in different ways [13,31,[34][35][36][37][38][39]. We first confirmed V-ATPase expression in human monocyte-derived macrophages [40] by Western blot (not shown) and by using immunofluorescence microscopy where no obvious differences regarding V-ATPase subcellular localization between the macrophage phenotypes were immediately apparent (Fig.…”
Section: Expression Of V-atpase In Macrophages and Effects Of The V-asupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies showed that macrophages from different origins and species express V-ATPase and respond to VATPase inhibitors in different ways [13,31,[34][35][36][37][38][39]. We first confirmed V-ATPase expression in human monocyte-derived macrophages [40] by Western blot (not shown) and by using immunofluorescence microscopy where no obvious differences regarding V-ATPase subcellular localization between the macrophage phenotypes were immediately apparent (Fig.…”
Section: Expression Of V-atpase In Macrophages and Effects Of The V-asupporting
confidence: 59%
“…Pharmacological manipulation of V-ATPase in macrophages by respective inhibitors such as bafilomycin A1 was reported before [13,31,35,37,38,48,50]. Many of these studies focused on osteoclasts [51], macrophage cell lines [31] and macrophages from rodents [37,39,48] and from other animals [52], but only few studies addressed V-ATPase functions in human primary macrophages [40,50], and to the best of our knowledge there are no reports that studied the role of V-ATPase on cytokine/chemokine secretion of different macrophage phenotypes, such as M1 and M2.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Acidic pH ex benefits tumor cells because it promotes invasiveness, whereas an alkaline pH cyt gives them a competitive advantage over normal cells for growth. Furthermore, V-ATPase is anti-apoptotic in tumor cells (49,59).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we supposed that apoptosis of osteoclasts and their precursors may contribute to the abovedescribed inhibition. New evidence demonstrates that triggering osteoclast apoptosis occurs via a variety of extracellular stimuli, such as estrogens [18][19][20], bisphosphonates [21] and bafilomycin A1 [22]. The consequences are diminished bone loss and reduced bone turnover.…”
Section: Discussionmentioning
confidence: 99%